Flipping the sociology classroom: Towards a practice of online pedagogy. (December 2013) - Forsey, Martin; Low, Mitchell; Glance, David
Profound changes are under way in university learning and teaching. Online education is taking hold as never before, catalysed in no small part by the advent of Massive Open Online Courses (MOOCs), free university units offered online to anyone with an internet connection. MOOCs appear to be intensifying the trend towards 'flipping' the classroom, which involves students engaging with course materials online – usually short videos and readings – then coming to classes constructed as workshops or symposia in which they are invited to practically apply their new knowledge in a variety of ways. This article reports on the ways in which MOOCs have allowed us to critically re-examine pedagogy and practice in the sociology classroom and to test our own assumptions regarding effective pedagogy via an action research project interrogating student reception of a flipped sociology class. Based on preliminary surveys, participant observation and formal interviews gauging student perceptions and initial reception to this particular class, the research reported here offers important correctives to debates that are usually based more on supposition than empirical evidence.